Integrated Metabolome and Transcriptome Analyses Provides Insights into Ovule Abortion in Camellia oleifera - Yayan Zhu; Jiajuan Xu; Gang Wang; Feng Xiao; Minggang Zhang; Qinmeng Zeng; Jie Xu (Plants)
Camellia oleifera is a unique woody edible oil tree species in China, and the ovule development affects the yield of seeds. This study selected three different types of C. oleifera clones and used LC-MS, RNA-seq, and other techniques to compare the endogenous hormone contents, gene expression levels, and metabolite changes between normal and aborted ovules. The results showed that high levels of ABA, JA, and SA may lead to the phenotype of ovule abortion. A total of 270 differential metabolites were identified in the metabolome, with L-methionine, citrulline, L-tryptophan, L-phenylalanine, and indolepyruvate being downregulated to varying degrees in the aborted ovules. Genes involved in plant hormone synthesis and response, such as GH3.1, IAA14, PIN1, AUX22, ARF1_2, BZR1_2, GA2ox, ERFC3, ABF2, and PYL8, responded to ovule development. This study elucidates the physiological, metabolic, and transcriptional responses to ovule abortion, providing a theoretical basis for understanding ovule development and yield regulation in C. oleifera.